Analysis of Printed Circuit Boards strains using finite element analysis and digital image correlation - Liviu Marsavina; Alexandru Falk; Octavian Pop (Fracture and Structural Integrity)
This paper investigates the use of digital image correlation (DIC) and finite element analysis for strain measurement on Printed Board Circuits (PCBs).